2018
DOI: 10.1016/j.ssci.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Making it stick: Exploring the effects of information and behavioral training on self-protectiveness of citizens in a real-life safety setting

Abstract: A B S T R A C TThis study contributes to our knowledge of whether and why citizens engage in self-protective behavior with regard to a real-life risk (the transportation of chemical substances by train). We assume that the way in which relevant risk information is processed, actively vs. passively, is a crucial factor. We hypothesize that behavioral training on self-protectiveness (the active approach) will increase respondents' perceived feasibility (self-efficacy) and the expected usefulness (response-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Risk communication need to be concentrated mainly on communication of risk-mitigation alternatives considered as useful by the target audience [ 26 ], identifying group-specific demands would be beneficial to render proper information to meet each population group’s needs [ 58 ]. Thus, the mutual relationship between risk communication and the status of risk perceived by community members is of great importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk communication need to be concentrated mainly on communication of risk-mitigation alternatives considered as useful by the target audience [ 26 ], identifying group-specific demands would be beneficial to render proper information to meet each population group’s needs [ 58 ]. Thus, the mutual relationship between risk communication and the status of risk perceived by community members is of great importance.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the associations of RC and RP [12,17]; however, there are reports on RC influence over RP in recent research [13,24,25] . It is recommended that RP is a prerequisite for protective behaviors [12,[26][27][28]. A review of the literature reveals that there is a decrease in articles published on a oneway flow of RC as well as an increase in those concerned with two-way communications [29]; hence, RC seems to have dynamism as well as interactivity encompassing negotiations among various groups of key players and audiences [16].…”
Section: Risk Communication and Risk Perceptionsmentioning
confidence: 99%
“…Santos et al [46] and Stolzer et al [47]; • self-reported behaviour used as measures of behaviour, such as individuals describing their own safety conduct, e.g. Kievik et al [48];…”
Section: Issue Giving Rise To This Commitmentmentioning
confidence: 99%
“…According to Konijn et al (2018), active training is associated with a stronger effect on the mind than passive teaching methods. Later on in the real world trained citizens are more likely to behave safely and self-defense than just Informed (Kievik et al, 2018).…”
Section: Teaching Methodsmentioning
confidence: 99%